Pengaruh Kepuasan Pelanggan, Iklan Online, dan Social Media Marketing terhadap Loyalitas Pelanggan (Survei Pada Pengikut Instagram @rucas.co Tahun 2021) - Rizka Sari; Rezi Erdiansyah (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Social Media needs advertising so that the online hop they run can be widely spread on social media very quickly. Customer loyalty is very important and must be considered by the company, because if the customer is loyal to a particular brand or company, the customer will help promote the company's products. to competitors' products.